PENGELOLAAN PERBATASAN DARAT DI PROVINSI KALIMANTAN TIMUR DARI PERSPEKTIF SOSIAL DAN EKONOMI PERTANIAN (STUDI KASUS: KECAMATAN KRAYAN, KABUPATEN NUNUKAN) - Sihaloho, Henrykus (Jurnal Manajemen dan Bisnis, 2012)
This study was a fisrst study when accompanying a working visitation of Special Committee of State Border of DPD RI (Senate of Republic of Indonesia) to East Borneo, West Borneo, and East Malaysia on March 29- April 2, 2011. This study concluded that poverty, stupidity, and underdevelopment were still a general phenomenon in borderland of East Borneo Province. This condition caused some citizens of Indonesia changing their citizenship and having double identity. There were impetus factors causing them changing their citizenship and having double identity, namely lack of administrative ability and lack of ability of Government to raise standard of living of borderer in economy, health, education, manpower, et cetera. This study also concluded that the borderland management needs three in one approach, that is combination of prosperity approach, security approach, and environment approach. The combination of three in one approach must stand on social and cultural reality because the borderland area was not homogenous and empty.